Case Report: Remdesivir and Convalescent Plasma in a Newly Acute B Lymphoblastic Leukemia Diagnosis With Concomitant Sars-CoV-2 Infection - Dell'Isola, Giovanni Battista; Felicioni, Matteo; Ferraro, Luigi; Capolsini, Ilaria; Cerri, Carla; Gurdo, Grazia; Mastrodicasa, Elena; Massei, Maria Speranza; Perruccio, Katia; Brogna, Mariangela; Mercuri, Alessandra; Pasqua, Barbara Luciani; et al. (Frontiers in Pediatrics, 2021)
Introduction: The spread of Covid-19 has worsened the prognosis of oncology patients interrupting or delaying life-saving therapies and increasing the risk of severe SARS-CoV-2 infections. Acute lymphoblastic leukemia (ALL) is the most frequent tumor in pediatric age and the management of this disease with concomitant SARS COV 2 infection represents a challenging situation. Case presentation: We present a case of a 6-year old female with a newly diagnosed ALL during a documented SARS-CoV-2 infection. Our patient was admitted after 20 days from SARS-CoV-2 detection for serotine fever. Laboratory testing showed severe neutropenia and moderate pulmonary involvement was detected at chest x-ray. Acute lymphoblastic leukemia diagnosis was made through morphological and molecular analysis on bone marrow aspirate. Due to the stability of the blood count and clinical conditions, antiviral therapy with Remdesivir and Convalescent Plasma was started before antiblastic therapy with a rapid resolution of the infection. Conclusion: According to our experience, the treatment with Remdesivir and Convalescent Plasma has led to a rapid resolution of Sars-Cov-2 infection. Our case did not present any adverse event to the therapy. Thus, this treatment could be considered in patients with malignancies in order to accelerate the resolution of the infection and begin immunosuppressive treatment safely. Further studies are required to confirm this hypothesis.